2015
DOI: 10.18632/oncotarget.4087
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibits Erk1/2-mediated neuronal apoptosis caused by cadmium

Abstract: Cadmium (Cd), an environmental contaminant, causes neurodegenerative disorders. Recently we have shown that rapamycin prevents Cd-induced neuronal cell death by inhibiting mTOR signaling pathway. Here we found that rapamycin exerted its prevention against Cd-induced neuronal cell death also partially via blocking Erk1/2 pathway. Inhibiting Erk1/2 with PD98059 or silencing Erk1/2 potentiated rapamycin's inhibition of Cd-induced phosphorylation of Erk1/2 and apoptosis in neuronal cells. Both PP2A and PTEN/Akt we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Further, because RPM is a famous mTOR inhibitor, we try to assess related proteins in the ERK1/2 and mTOR pathways. Consistent with previous reports ( 28 , 29 ), the results revealed that both p-ERK1/2/ERK1/2 and p-mTOR/mTOR exhibited increased levels following lncRNA SENCR upregulation. Based on the above data and analysis, we conclude the likely mechanism of action of lncRNA SENCR via relieving the inhibitory effect of RPM on ERK1/2 and mTOR pathways and promoting HUVEC proliferation and migration.…”
Section: Discussionsupporting
confidence: 92%
“…Further, because RPM is a famous mTOR inhibitor, we try to assess related proteins in the ERK1/2 and mTOR pathways. Consistent with previous reports ( 28 , 29 ), the results revealed that both p-ERK1/2/ERK1/2 and p-mTOR/mTOR exhibited increased levels following lncRNA SENCR upregulation. Based on the above data and analysis, we conclude the likely mechanism of action of lncRNA SENCR via relieving the inhibitory effect of RPM on ERK1/2 and mTOR pathways and promoting HUVEC proliferation and migration.…”
Section: Discussionsupporting
confidence: 92%
“…Because of the high blood–brain barrier (BBB) permeability of this compound, Cd toxicity is highly significant in the nervous system. Epidemiological and clinical data have shown that Cd exposure severely affects the function of the nervous system and is associated with neurological disorders with symptoms including headache, vertigo, olfactory dysfunction, memory deficits, polyneuropathy, lower attention, and parkinsonism symptoms …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and clinical data have shown that Cd exposure severely affects the function of the nervous system and is associated with neurological disorders with symptoms including headache, vertigo, olfactory dysfunction, memory deficits, polyneuropathy, lower attention, and parkinsonism symptoms. [4][5][6] Autophagy is a "self-eating" catabolic process that removes protein aggregates and damaged organelles required to maintain a homeostatic environment within the cell. Depending on the environmental stress and cell type, the autophagy pathway acts as either a survival or death safeguard mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In apoptotic cells, caspase-9 is activated [15] , and this leads to the activation and cleavage of executioner caspases-3 and -7 [16,17] . The critical downstream protein PARP is cleaved in this process [18] .…”
Section: Introductionmentioning
confidence: 99%